2006
DOI: 10.1111/j.1365-2249.2006.03169.x
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine inhibits the production of proinflammatory mediators in human monocytes by suppression of I-κB phosphorylation and nuclear factor-κB transcriptional activity through nicotinic acetylcholine receptor α7

Abstract: Summary Macrophages/monocytes and the proinflammatory mediators, such as tumour necrosis factor (TNF)‐α, prostaglandin E2 (PGE2), macrophage inflammatory protein (MIP)‐1α and MIP‐1α, play a critical role in the progression of immunological disorders including rheumatoid arthritis, Behçet’s disease and Crohn’s disease. In addition, the nicotinic acetylcholine receptor‐α7 (α7nAChR) subunit is an essential regulator of inflammation. In this study, we evaluated the expression of the α7nAChR subunit on human periph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
222
0
9

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(245 citation statements)
references
References 32 publications
14
222
0
9
Order By: Relevance
“…3). Indeed, the existence of a brain cholinergic anti-inflammatory pathway mediated by ␣7-nAChR is now well substantiated: macrophages, microvascular endothelial cells, and microglia express ␣7-nAChR on their surface, and the activation of these receptors resulted in immunosuppressive effects (350,370,451).…”
Section: Nicotinic-cholinergic Transmissionmentioning
confidence: 99%
“…3). Indeed, the existence of a brain cholinergic anti-inflammatory pathway mediated by ␣7-nAChR is now well substantiated: macrophages, microvascular endothelial cells, and microglia express ␣7-nAChR on their surface, and the activation of these receptors resulted in immunosuppressive effects (350,370,451).…”
Section: Nicotinic-cholinergic Transmissionmentioning
confidence: 99%
“…22 Moreover, in other studies, nicotine was observed to significantly decrease the secretion of inflammatory mediators in human monocyte-macrophages by inhibiting activation of nuclear factor (NF)-κB. 32,33 It has been suggested that nicotine could be an important regulator of monocytemacrophages, through its role in the cholinergic antiinflammatory pathway, [34][35][36] mediated, in part, by inhibiting NF-κB and activating the transcription factor STAT3, a negative regulator of inflammation, via interaction with acetylcholine receptor α-7. 37 Contrary to the evidence showing antiinflammatory properties of smoking in monocytemacrophages, most 38,39 but not all studies 40 have reported a negative correlation between cigarette smoking and adiponectinemia, a well-known antiinflammatory adipokine that increases PPARG and insulin sensitivity.…”
Section: Circulation Journal Vol73 November 2009mentioning
confidence: 99%
“…The ␣7nAChR is expressed by various immune cells, including monocytes (15), macrophages (5,16), T and B lymphocytes (17,18), and dendritic cells (19). In addition to this classic ␣7nAChR, the human genome contains an alternative ␣7 transcript designated dup␣7 or "cholinergic receptor family with sequence similarity to 7A" (CHRFAM7A) (20).…”
mentioning
confidence: 99%